Subtle differences in chemical pattern between human toll‐like receptor 8 agonists and antagonists: Emerging chemical patterns analysis. (9th August 2019) - Huang, Shuheng; Mei, Hu; Zhang, Duo; Shi, Tingting; Chen, Linxin; Kuang, Zuyin; Heng, Yu; Pan, Xianchao; Lu, Laichun
Abstract: Due to the potencies in the treatments of cancer, infectious diseases, and autoimmune diseases, the developments of human TLR8 (hTLR8) agonists and antagonists have attracted widespread attentions. The hTLR8 agonists and antagonists have similar structures but with completely opposite biological effects. Up to date, the subtle differences in the structures between the hTLR8 agonists and antagonists are still unknown. In this work, emerging chemical pattern (ECP) was successfully used to extract the key chemical patterns of the hTLR8 agonists and antagonists. By using CAEP classifier, an optimal ECP model with only 3 descriptors was established with the overall prediction accuracy larger than 90%. Further hierarchical cluster analysis and molecular docking showed that the H‐bond and hydrophobic properties are the key features distinguishing the hTLR8 agonists from antagonists. Comparing with the antagonists, the agonists show stronger specific H‐bond properties, while antagonists have stronger non‐specific hydrophobic properties. The significant differences in the structural properties may be closely related to the activation/inhibition mechanism of hTLR8. Abstract : Recently, the developments of human toll‐like receptor 8 (hTLR8) agonists and antagonists have aroused wide attentions. The hTLR8 agonists and antagonists have similar structures but with completely opposite biological effects. However, the subtle differences in the structures between the hTLR8 agonists and antagonists are still unclear. Herein, emerging chemical pattern was successfully used to extract the dominant differences in the structural profiles between hTLR8 agonists and antagonists. The results obtained in this paper can be widely applied to the drug design and virtual screening of hTLR8 agonists and antagonists as well as the mechanism researches.